Effects of ice load prediction model and thickness on the structural loads of an offshore wind turbine - Lai, Yongqing; He, Ben; Ding, Jieyi; Lyu, Na; Yang, Yang (Frontiers in Energy Research, 2025)
Offshore wind turbines (OWTs) installed in cold regions are prone to risking ice collisions, leading to potential damage of the support structure. It is imperative to quantitatively investigate the ice loading effect on the structural loads of OWTs. In order to address this research need, a novel module capable of predicting ice loads on OWTs based on six empirical models has been developed, and subsequently integrated within Bladed for considering the coupled effects of ice and wind loading when performing dynamic analysis of OWTs. The structural loads of a monopile-supported 5 MW OWT under operational state are predicted for different wind-ice combined conditions. The effects of ice load prediction model and ice thickness on the structural loads are examined. The results show that ice load prediction model significantly affects the structural loads of the OWT, especially for low wind speed conditions. The maximum increase in mudline shear force is around 242.54% as predicted by the continuous random crushing model for 1 m thickness ice, while the coned structure is able to reduce the ice-induced load by around 85%. Moreover, it is found that the shear force and pitching bending moment at the pile-base are enhanced linearly to the increase of ice thickness. The pitching bending moment is increased by up to 267.83% and 59.21% at 0.1 m and 0.5 m ice thickness, respectively. This study has indicated that ice loading must be considered for the design of OWTs in cold regions.